PENGARUH pH MEDIA MRSA TERHADAP PERTUMBUHAN BAKTERI Lactobacillus casei DAN Lactobacillus reuteri - Maria Berlina Purba; Yus Hargono Cahyaning Yudi; Maria Arieni Eka Devina Sihotang; Yulin Wilasti (Program Studi Teknologi Laboratorium Medik, 2021)
Humans can obtain health benefits by consuming probiotics such as Lactobacillus casei and L. reuteri. To test the viability of probiotics, an optimum pH of the medium is needed for their growth. This study used 2 products, namely yogurt and powdered milk, with 2 solvent treatments (PSS and MRSB) and 2 pH MRSA media, namely pH 5.6 and 6.5. The ALT was determined after a 72-hour anaerobic incubation at 38°C.The results showed that L. casei grew both at pH 5.6 and at pH 6.5. The results of the t-test, with a significance level of 0.05, showed that there was a significant difference when using different solvents. L. reuteri grew best in MRSB solvent with MRSA media pH 6.5 (probiotic count 6.6 x 106 colonies/mL).